2016
DOI: 10.1017/pasa.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Dawes Review 5: Australian Aboriginal Astronomy and Navigation

Abstract: The traditional cultures of Aboriginal Australians include a significant astronomical component, perpetuated through oral tradition, ceremony, and art. This astronomical knowledge includes a deep understanding of the motion of objects in the sky, which was used for practical purposes such as constructing calendars and for navigation. There is also evidence that traditional Aboriginal Australians made careful records and measurements of cyclical phenomena, recorded unexpected phenomena such as eclipses and mete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 100 publications
(330 reference statements)
0
11
0
Order By: Relevance
“…Astronomy is a central part of many Aboriginal cultures. An extensive review, citing all known publications in this field, is given by Norris (2016). Mountford (1976) reported that some Aboriginal people knew the name of every star as faint as fourth magnitude, and knew myths associated with most of those stars.…”
Section: Aboriginal Astronomymentioning
confidence: 99%
See 4 more Smart Citations
“…Astronomy is a central part of many Aboriginal cultures. An extensive review, citing all known publications in this field, is given by Norris (2016). Mountford (1976) reported that some Aboriginal people knew the name of every star as faint as fourth magnitude, and knew myths associated with most of those stars.…”
Section: Aboriginal Astronomymentioning
confidence: 99%
“…Mountford (1976) reported that some Aboriginal people knew the name of every star as faint as fourth magnitude, and knew myths associated with most of those stars. Even now, some elders can name most stars in the sky visible to the naked eye, and have an intuitive understanding of how the sky rotates over their heads from east to west during the night, and how it shifts over the course of a year (Norris, 2016). Maegraith (1932) says that 'The most interesting fact about Aboriginal astronomy is that all the adult males of the tribe are fully conversant with all that is known, while no young man of the tribe knows much about the stars until after his initiation is complete ...…”
Section: Aboriginal Astronomymentioning
confidence: 99%
See 3 more Smart Citations